2009
DOI: 10.1111/j.1466-7657.2008.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a nursing smoking cessation intervention on military students in Turkey

Abstract: The interventions by the nurses in the smoking cessation programme were effective, resulting in a positive change in attitude and behaviour that would support the students' smoking cessation and the process of cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…Of the 100 included studies, 46 included young male participants only with 18 (18% of total studies and 39.1% of young adult male only studies) [5254, 57, 58, 60, 61, 6473, 76] for physical inactivity, 14 (14% of total studies and 30.4% of young adult male only studies) for unsafe sexual behaviour [51, 80, 82, 8591, 94, 96–98], 4 (4% of total studies and 8.7% of young adult male only studies) for alcohol use [126129], 2 (2% of total studies and 4.3% of young adult male only studies) for unsafe vehicle driving [104, 105] 1 (1% of total studies and 2.2% of young adult male only studies) for tobacco smoking [110], 1 (1% of total studies and 2.2% of young adult male only studies) for poor diet [103], and 1 (1% of total studies and 2.2% of young adult male only studies) for tanning/sun exposure [115]. Also 5 (5% of total studies and 10.9% of young adult male only studies) of the studies with only young adult male participants targeted multiple risk behaviours [116, 119, 122, 124, 125].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 100 included studies, 46 included young male participants only with 18 (18% of total studies and 39.1% of young adult male only studies) [5254, 57, 58, 60, 61, 6473, 76] for physical inactivity, 14 (14% of total studies and 30.4% of young adult male only studies) for unsafe sexual behaviour [51, 80, 82, 8591, 94, 96–98], 4 (4% of total studies and 8.7% of young adult male only studies) for alcohol use [126129], 2 (2% of total studies and 4.3% of young adult male only studies) for unsafe vehicle driving [104, 105] 1 (1% of total studies and 2.2% of young adult male only studies) for tobacco smoking [110], 1 (1% of total studies and 2.2% of young adult male only studies) for poor diet [103], and 1 (1% of total studies and 2.2% of young adult male only studies) for tanning/sun exposure [115]. Also 5 (5% of total studies and 10.9% of young adult male only studies) of the studies with only young adult male participants targeted multiple risk behaviours [116, 119, 122, 124, 125].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining interventions were carried out in Europe (n = 18, 18%) [52, 53, 55, 56, 60, 61, 70, 81, 95, 98, 102, 104, 110, 116, 119, 127, 128, 148], Australasia (n = 8, 8%) [54, 65, 66, 105, 108, 120, 124, 149], Asia (n = 6, 6%) [64, 67, 71, 72, 107, 114], South America (n = 3, 3%) [69, 79, 83], Africa (n = 1, 1%) [76] and one intervention (1%) was implemented in multiple countries across two continents (USA, Ecuador, Peru and Brazil) [84]. The risk behaviours that were targeted in various intervention countries, separated by studies with young adult male participants only and studies with outcomes stratified by age/sex to include young adult males are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because nursing interventions play a very important role in the promotion of optimal health care, TTM is well suited to nursing studies and has been used in other nursing research (Fahrenwald 2005, Kim 2007). For example, a smoking cessation study in Turkey by nurses using the TTM was effective (Ergul & Temel 2009). Our study and other studies have also shown that nurses can play a prominent role in assisting patients to quit smoking.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, TTM interventions increase the success of behavioral change, especially of smoking cessation (12). In Turkey, the TTM has been indicated to be effective in various smoking cessation studies focusing on different populations, such as adolescents (12), high school students (13), pregnant women (14), young military recruits (15), and adults (16). However, there has been no study conducted on adult women in Turkey in which researchers have used all the TTM scales developed for adult smokers.…”
Section: Introductionmentioning
confidence: 99%